2018
DOI: 10.1007/s11695-018-3314-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That the Length of Bile Loop Determines Serum Bile Acid Concentration and Glycemic Control After Bariatric Surgery

Abstract: Background Bariatric surgery contributes to the improvement in glucose metabolism that may be related to a postoperative increase in serum bile acids (BAs). Three commonly used types of bariatric procedures, laparoscopic sleeve gastrectomy (LSG) (without creation of a bile loop), Roux-en-Y gastric bypass (RYGB), and omega-loop gastric bypass (OLGB) (with creation of shorter 100-150 cm and longer 200-280 cm bile loops, respectively), differ in their effects on glycemic control. The aim of the study was to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…At present, the most effective is BS. OAGB is a bariatric procedure that improves metabolic parameters [5], causes remission of type 2 diabetes mellitus [4], and is associated with low morbidity [22].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the most effective is BS. OAGB is a bariatric procedure that improves metabolic parameters [5], causes remission of type 2 diabetes mellitus [4], and is associated with low morbidity [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that the length ratio of the biliopancreatic limb and the common limb represent a major determinant of postoperative serum bile acid concentrations. Postoperative serum bile acid concentrations are likely to be greater with longer biliopancreatic limb and shorter common limb, as evidenced by both animal (Han et al, 2015; Miyachi et al, 2016) and human studies (Mika et al, 2018). The precise mechanism has yet been elucidated.…”
Section: Mechanisms Of Serum Bile Acid Elevation After Bariatric Surgerymentioning
confidence: 99%
“…Bariatric surgery brings about significant alterations in lipid metabolism, but the exact nature of these changes depends on the surgical procedure [3]. One anastomosis gastric bypass (OAGB) is a promising type of bariatric surgery that improves metabolic parameters (reduction in serum concentrations of triglycerides, total and LDL cholesterol, and C-reactive protein; and increase in HDL cholesterol concentration) [4], causes remission of type 2 diabetes mellitus, and is associated with relatively low morbidity [5,6]. However, some studies found higher incidence of diarrhea, steatorrhea, and nutritional adverse events after OAGB than after RYGB [7].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced food intake after surgery may result in deficiencies of some important nutrients [8], such as bioactive lipids which, although present in small amounts in the diet, are vital for many physiological functions. On the other hand, bariatric surgery may lead to an increase in serum concentrations of some other lipid classes, e.g., bile acids [3,4,9].…”
Section: Introductionmentioning
confidence: 99%